Hambatan dan Tantangan Pelaksanaan Pendidikan Kewarganegaraan di Perguruan Tinggi - Maskarto Lucky Nara Rosmadi (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
Citizenship education is a compulsory subject in all universities based on the Law onNational Education System. The purpose of this research is to know the implementationof civic education in universities as well as obstacles and challenges in theimplementation. The research method used is descriptive analytical with qualitativeapproach. Data collection techniques consist of primary data obtained fromrespondents and secondary data in the form of literature, scientific journals bothnationally and internationally. From the result of research, it is found that giving thecourse of civic education by lecturer is only theoretical only without accompanied bythe implementation of student activities. In addition, the lecturers who hold the subjectsof civic education have no competence in the field of state defense and do not getspecial training as lecturer of civic education from any institution. This requiressupport from the central government through the National Resilience Institute byproviding training in the form of lecturer candidates courses for Pancasila Educationand Citizenship Education courses.